The effect of gender diversity on corporate performance in South African listed companies - Peens, Nicolene (My University, 2018)
ABSTRACT The issue of diversity in the workplace, especially gender diversity, has been in the spotlight in recent times. Partly due to increased media attention, activism by certain interest groups, and a general global focus on the importance of equality in the world of work. This study endeavoured to better understand the effect, if any, of greater gender diversity of boards of directors on corporate financial performance. The directorate and financial performance of the top hundred companies listed on the Johannesburg Stock Exchange from 2010 to 2014 was analysed to investigate the phenomenon of gender diversity in the boardroom. The relationship between the percentage women on the board of directors and corporate financial performance was examined using multiple regression analysis and Structural Equation Modelling. Both Tobin’s Q and Return on Assets were used as financial performance measures. Similar to a number of studies on the topic, no statistically significant relationship could be observed between board gender diversity and company financial performance. The results of this study does not support the business case for greater board gender diversity, but also does not find evidence that appointing women to the board comes at a cost to organisations. The issue of addressing the underrepresentation of women in decision-making roles of the South African workforce remains of critical importance in achieving a more inclusive and equal workforce where greater variety can benefit individuals, society, as well as organisations.
MBA Thesis
Keywords: Women executives -- South Africa. Directors of corporations -- South Africa. Diversity in the workplace -- South Africa.